Military trends in China: Modernising and internationalising the People's Liberation Army - Sophie-Charlotte Brune; Sascha Lange; Janka Oertel (Stiftung Wissenschaft und Politik (SWP), 2010)
The steady rise in China's defence budget over recent years naturally stokes the speculation. From just 9.8 billion in 1997 it more than quadrupled within a decade, according to the official figures, to reach 46.8 billion by 2007 (although the proportion of annual GDP rose by just 0.29 percentage points over the same period). Beijing's official defence budget for 2009 is 70.2 billion, but the real level of Chinese military spending is disputed. Because they leave important expenditures on strategic capabilities and military space programmes unaccounted for, the official figures say little about the actual state of China's armed forces (PLA).The PLA is still a fundamentally defensive force, although its offensive potential is growing in the fields of nuclear weapons and space-based systems, as well as air and naval forces. Military modernisation has progressed furthest in the realm of the strategic forces and the navy, while the greatest deficits remain in the air force, where a lack of force multipliers such as reconnaissance aircraft and aerial refuelling tankers is the main obstacle to greater strength and force projection.The Western arms embargo ensures that the import of such force multipliers and access to the relevant technologies remain restricted. If it is in the interests of the EU and the United States to deny China access to these technologies at least in the short to medium term, the embargo will have to be maintained on key technologies.The rapid expansion of China's military capabilities has not thus far been accompanied by adequate political communication. An increase in transparency on security and military matters could help to reassure other states. Effective international integration would support this process
Keywords: 320